2015
DOI: 10.1097/dcr.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Incontinence

Abstract: Fecal incontinence is a prevalent condition of equal sex distribution, affecting ≈1 in 8 community adults, and has identifiable associated factors. The paucity of high-quality prevalence studies emphasizes the need for future population-based studies that use standardized diagnostic criteria for fecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(58 citation statements)
references
References 60 publications
(71 reference statements)
4
53
0
1
Order By: Relevance
“…International studies and studies in Scandinavia have reported the prevalence of urinary incontinence in similar groups to be equally high or higher (Buckley et al, 2010;Ebbesen et al, 2013;Milsom et al, 2014;Sorbye et al, 2009;Spigset et al, 1989) and faecal incontinence to be considerably lower (Finne-Soveri et al, 2008;Ng et al, 2015;Roberts et al, 1999;Rommen et al, 2012;Wu et al, 2015) than the prevalence of toileting difficulties reported in our study. Our study provides information on challenges experienced and also on the need for help caused by these challenges, but we do not have information on whether assisting needs are linked specifically to toilet visits, urinary incontinence and/or faecal incontinence.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…International studies and studies in Scandinavia have reported the prevalence of urinary incontinence in similar groups to be equally high or higher (Buckley et al, 2010;Ebbesen et al, 2013;Milsom et al, 2014;Sorbye et al, 2009;Spigset et al, 1989) and faecal incontinence to be considerably lower (Finne-Soveri et al, 2008;Ng et al, 2015;Roberts et al, 1999;Rommen et al, 2012;Wu et al, 2015) than the prevalence of toileting difficulties reported in our study. Our study provides information on challenges experienced and also on the need for help caused by these challenges, but we do not have information on whether assisting needs are linked specifically to toilet visits, urinary incontinence and/or faecal incontinence.…”
Section: Discussionsupporting
confidence: 47%
“…Even so, several studies have assessed urinary and/or faecal incontinence (Buckley et al, 2010;Ng, Sivakumaran, Nassar, & Gladman, 2015). One European study of community-dwelling older people of both genders receiving formal in-home care reported the prevalence of urinary incontinence to be 46% (Du Moulin, Hamers, Ambergen, Janssen, & Halfens, 2008), while it is reported to be 37% among community-dwelling older people of both genders receiving formal in-home care in Norway (Sorbye et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1 FI is associated with a substantial degree of embarrassment, hygiene issues, poor self-esteem, and significantly-impaired quality of life. 2 Although there is controversy as to whether women are more likely to develop FI than men, 3 women potentially have unique risk factors for FI, specifically anal sphincter trauma secondary to obstetric injury and pelvic floor changes related to menopause.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal incontinence is a debilitating condition that affects approximately 2%–20% of the adult population [ 1 2 ]. It is more common in females, and with advancing age, it is the second most common cause of admission to a nursing home [ 3 ].…”
Section: Introductionmentioning
confidence: 99%